Intergenerational Mobility and Preferences for Redistribution - Alesina, Alberto; Stantcheva, Stefanie; Teso, Edoardo (American Economic Review, 2018)
Using new cross-country survey and experimental data, we investigate how beliefs about intergenerational mobility affect preferences for redistribution in France, Italy, Sweden, the United Kingdom, and the United States. Americans are more optimistic than Europeans about social mobility. Our randomized treatment shows pessimistic information about mobility and increases support for redistribution, mostly for “equality of opportunity” policies. We find strong political polarization. Left-wing respondents are more pessimistic about mobility: their preferences for redistribution are correlated with their mobility perceptions; and they support more redistribution after seeing pessimistic information. None of this is true for right-wing respondents, possibly because they see the government as a “problem” and not as the “solution.” (JEL D63, D72, H23, H24, J31, J62)